2008
DOI: 10.1097/bot.0b013e318162a0d2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Ipsilateral Intertrochanteric and Femoral Shaft Fractures

Abstract: For most outcome measures, no significant differences in functional outcome scores were observed between the 2 treatment groups. The results of this study suggest the need for a randomized controlled trial with a larger sample size to more definitively compare the 2 fixation constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…A comparison with previous studies is difficult, since there are only a few papers reporting longitudinal SMFA data [34,42] and, as far as we know, only one on hip fracture patients. In a recently published retrospective cohort study with a mean 50-month follow-up on 26 multitrauma patients with ipsilateral intertrochanteric hip and femoral shaft fractures, Peskun and coworkers [43] reported results in the Dysfunction Index that were comparable to ours, while their results for the Bother Index were worse, probably reflecting the outcome after a more severe injury in a multitrauma population. The internal responsiveness was good for both the Dysfunction and Bother Indices based on the relatively large observed change between the prefracture status and the 4-month follow-up and the moderate to large SRMs, moderate for the Bother Index and large for the Dysfunction Index.…”
Section: Discussionsupporting
confidence: 60%
“…A comparison with previous studies is difficult, since there are only a few papers reporting longitudinal SMFA data [34,42] and, as far as we know, only one on hip fracture patients. In a recently published retrospective cohort study with a mean 50-month follow-up on 26 multitrauma patients with ipsilateral intertrochanteric hip and femoral shaft fractures, Peskun and coworkers [43] reported results in the Dysfunction Index that were comparable to ours, while their results for the Bother Index were worse, probably reflecting the outcome after a more severe injury in a multitrauma population. The internal responsiveness was good for both the Dysfunction and Bother Indices based on the relatively large observed change between the prefracture status and the 4-month follow-up and the moderate to large SRMs, moderate for the Bother Index and large for the Dysfunction Index.…”
Section: Discussionsupporting
confidence: 60%
“…Most previous reports have shown that clinical outcomes of management of ipsilateral intertrochanteric and femoral shaft fractures are satisfactory and have acceptable complications 3,6,10,17 . Nonunion of intertrochanteric fractures has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been recommended for managing ipsilateral intertrochanteric and femoral shaft fractures 3–6,8,10,16,17 . Among them, reconstruction nail, sliding hip screw combined with retrograde nail or plate combinations are the most frequently used methods 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A research group from the University of Minnesota analyzed Medicare claims and enrollment data between 2000 and 2002 for 212,821 patients who had been managed for an intertrochanteric hip fracture and determined that there was geographic variation in the choice of implant used to fix these fractures 91 93 . Internal fixation of these concomitant fractures was performed with a reconstruction nail (n = 13) or a sliding hip screw and a retrograde nail combination (n = 13).…”
Section: Lower Extremitymentioning
confidence: 99%